Umbilical hernia in Xhosa infants and children. - James, T (1982)
During the period 12 March 1980 to 10 March 1981 a consecutive series of 1200 Xhosa (Black) infants and young children, ranging in age from the newborn to the prepubertal, who attended the general outpatients department for a variety of medical complaints were examined for umbilical herniation. None had undergone any surgical operation, and patients with conditions possibly associated with umbilical herniation were excluded. Evidence of umbilical protrusion was found in 742 (61.8%), with a similar incidence in males and females. The overall incidence was reflected in each age group by a preponderance of children with umbilical hernia. This study confirms the validity of a generally-held impression that in Black children there is a strong tendency towards the persistence of umbilical hernia when it appears after separation of the cord.